Synthesis of cyclo-L-prolyl-glycine and study of its anti-parkinsonian activity - Ksenia Koliasnikova; Anna Golubyatnikova; Alexey Rebeko; Marina Vukolova; Polina Povarnina; Elena Kuznetsova (Фармакокинетика и Фармакодинамика, 2019)
The aim of the work was to develop an optimal scheme for the synthesis of substance of cyclo-L-prolylglycine neuropeptide (CPG), a potential drug useful for the integrated treatment of psychiatric pathologies, including anxiety, depressive disorders and cognitive impairment. Two 4-stage CPG synthesis schemes were considered. Both schemes led to a product with the same optical purity, comparable to the overall yield and time-consuming, however, the first scheme is 2.5 times more profitable in terms of the cost of basic reagents per 100 g of product. The first scheme was selected as the basis for the development of laboratory regulations. Also for the first time the anti-parkinsonian activity of CPG (0.05 and 0.5 mg/kg intraperitoneally) on a model of haloperidol catalepsy was detected.